The inevitable surge of online learning through the lens of English education lecturers during the unprecedented times - Debora Chaterin Simanjuntak; Nelson Balisar Panjaitan (Journal on English as a Foreign Language, 2021)
The onset of the COVID-19 pandemic has obliged universities worldwide to shift to other modalities such as e-learning. Lecturers feel obliged to motivate and aspire their students virtually. This study explores the perceptions and experience of English education lecturers on the inevitable surge of virtual teaching during the Pandemic. This study was a qualitative interview study utilized an interpretive description approach. The data were generated by interviewing 19 English education lecturers based on defined evaluation criteria and an online learning environment. Participants were given ten open-ended interview questions to find out how lecturers undertook online teaching during unprecedented times and perceived some changes in the teaching and learning process. The findings showed three themes emerged from lecturers’ perspectives during the shift to online learning; those themes are the need for iterative process, revamp delivery, and the need to advance technology infrastructure. In addition, there were two (themes that characterize the participants’ experiences in implementing online learning: Agility and adaptability, identification of the underlying needs. All themes in this study emerged from obtained sub-themes. These findings indicated that the inevitable surge of online learning shapes lecturers’ teaching skills and attitude in the process of shifting to other modalities.